Enhancing the Role of SMEs in the Arab World-Some Key Considerations - Stepanyan, Vahram (Policy Papers; Policy Paper ;, 2019)
Small and medium-sized enterprises (SMEs) are a cornerstone of Arab economies, accounting for over 90 percent of all businesses and providing a major source of new job creation. Governments across the Arab World recognize the important role that SMEs can play in delivering higher and more inclusive growth. Many have rightly placed SME development at the center of growth and jobs strategies to meet the needs of young populations. Authorities have initiated policy interventions and schemes to support SME development. But progress so far has been patchy, and more comprehensive policy action is needed. Fostering vibrant and competitive SMEs that contribute to employment opportunities and high value-added output requires various stakeholders to deliver on a broad range of factors. Arab governments need a holistic policy approach that addresses the gaps in access to finance, creates an enabling business environment, and upgrades human capital and infrastructure. The approach should also promote an entrepreneurial mindset.